The effect of a rehabilitation program for the injured supraspinatus muscle and the injured small rotator in improving some kinematic variables for air weapons players 10m with special needs - Enad, Liqaa Ali; Abdulhameed, Suhad Haseeb (International Journal of Psychosocial Rehabilitation, 2020)
In recent times, physical education in its various branches, especially in developed countries, has become an intertwining element and perhaps essential with the rest of the other medical, educational and social sciences to take care of the disabled, rehabilitate them and develop their mobility and physical abilities to integrate them into society and make them productive individuals in it. Physical therapists, a sports trainer who specializes in rehabilitating and training the disabled, a social researcher, a psychological expert and a professional expert. These are all those who deliver the handicapped to safety so that he can face the burdens of his life naturally and depend on himself in achieving his requirements.